2021
DOI: 10.1021/acsnano.1c03151
|View full text |Cite
|
Sign up to set email alerts
|

Microvilli Adhesion: An Alternative Route for Nanoparticle Cell Internalization

Abstract: The cellular uptake of nanoparticles (NPs) represents a critical step in nanomedicine and a crucial point for understanding the interaction of nanomaterials with biological systems. No specific mechanism of uptake has been identified so far, as the NPs are generally incorporated by the cells through one of the few well-known endocytotic mechanisms. Here, an alternative internalization route mediated by microvilli adhesion is demonstrated. This microvillus-mediated adhesion (MMA) has been observed using ceria a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 50 publications
(103 reference statements)
0
22
0
Order By: Relevance
“…We first synthesized water-soluble QDs coated with 40% octylamine-modified polyacrylic acid, which has been recently reported to facilitate microvillus-mediated adhesion and cell internalization . The hydrodynamic diameter of the QD was determined to be 87 nm in our previous work .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We first synthesized water-soluble QDs coated with 40% octylamine-modified polyacrylic acid, which has been recently reported to facilitate microvillus-mediated adhesion and cell internalization . The hydrodynamic diameter of the QD was determined to be 87 nm in our previous work .…”
Section: Resultsmentioning
confidence: 99%
“…A recent report suggested that polyacrylic acid coating facilitated microvilli adhesion and internalization of nanoparticles. 26 Our FAAs possibly first attached to the exterior of the plasma membrane of DCs, followed by internalization and intracellular migration (Figure 2a). From the asymmetrical shape of the image and intensity trajectories of FAAs, we determined that most FAAs consisted of clusters of QDs (Figures 2b and S6).…”
Section: ■ Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The 50 nm diameter of clathrin-coated pits on the hepatocyte plasma membrane may explain appearance of 20 nm but not 200 nm PSNS in putative endosomes. A recent report in cell culture (Sommi et al, 2021) demonstrates a role for microvillus-mediated adhesion as an alternative route for internalization of nanoparticles with an upper diameter limit of 70-80 nm. Further, a polyanionic surface is necessary for this interaction.…”
Section: Discussionmentioning
confidence: 99%